Visual Imagery And Its Relationship To Positive Thinking Among Fencing Athletes (Journal of the College of Basic Education, 2026)
The importance of this research lies in identifying the relationship between visual imagery and positive thinking among fencing athletes, given its direct impact on athletes’ performance levels, as psychological factors play a major role in achieving goals. The study aims to determine the levels of both visual imagery and positive thinking among fencing athletes, as well as to identify the relationship between these two variables. The researchers employed the descriptive method in a survey style, as it is suitable for the nature of the research problem.The research population consisted of fencing athletes representing clubs in Kirkuk Governorate, totaling (33) athletes from the following clubs: Kirkuk, Lailan, Al-Thawra, Sulaf, Ashti, Kirkuk Girls, and Kiwan. Three athletes were selected for the pilot study, while the research sample included (30) athletes who were intentionally selected, representing (90.9%) of the research population. The study utilized scales of visual imagery and positive thinking to obtain and statistically analyze the results.The researchers concluded that fencing athletes demonstrate a high level of both visual imagery and positive thinking, and that there is a statistically significant relationship between the two variables. The researchers recommend giving attention to positive thinking and other positive psychological variables, as they contribute to enhancing athletes’ performance levels and assisting them in achieving success, as well as conducting similar studies on other sports.